Attributions of Responsibility and Blame for Procrastination Behavior - Rahimi, Sonia; Hall, Nathan C.; Pychyl, Timothy A. (Frontiers in Psychology, 2016)
The present study examined the relationship between procrastination, delay, blameworthiness, and moral responsibility. Undergraduate students (N = 240) were provided two scenarios in which the reason for inaction (procrastination, delay), the target (self, other), and the outcome (positive, negative) were manipulated, and students were asked to rate the moral responsibility and blameworthiness of the agent. Results indicated that individuals who procrastinated were seen as more morally responsible and blameworthy than those who otherwise experienced delay. More specifically, after a negative outcome, procrastination was associated with more moral responsibility, whereas delay was associated with less moral responsibility. After a positive outcome, individuals perceived procrastination as deserving of less moral responsibility, and delays as associated with more moral responsibility. Finally, a three-way interaction showed that participants rated procrastination that resulted in failure as deserving of responsibility when engaged in by others as opposed to oneself.